Bacteriophage PBC1 and Its Endolysin as an Antimicrobial Agent against Bacillus cereus - Kong, Minsuk (Appl Environ Microbiol, 2015)
Bacillus cereus is an opportunistic human pathogen responsible for food poisoning and other, nongastrointestinal infections. Due to the emergence of multidrug-resistant B. cereus strains, the demand for alternative therapeutic options is increasing. To address these problems, we isolated and characterized a Siphoviridae virulent phage, PBC1, and its lytic enzymes. PBC1 showed a very narrow host range, infecting only 1 of 22 B. cereus strains. Phylogenetic analysis based on the major capsid protein revealed that PBC1 is more closely related to the Bacillus clarkii phage BCJA1c and phages of lactic acid bacteria than to the phages infecting B. cereus. Whole-genome comparison showed that the late-gene region, including the terminase gene, structural genes, and holin gene of PBC1, is similar to that from B. cereus temperate phage 250, whereas their endolysins are different. Compared to the extreme host specificity of PBC1, its endolysin, LysPBC1, showed a much broader lytic spectrum, albeit limited to the genus Bacillus. The catalytic domain of LysPBC1 when expressed alone also showed Bacillus-specific lytic activity, which was lower against the B. cereus group but higher against the Bacillus subtilis group than the full-length protein. Taken together, these results suggest that the virulent phage PBC1 is a useful component of a phage cocktail to control B. cereus, even with its exceptionally narrow host range, as it can kill a strain of B. cereus that is not killed by other phages, and that LysPBC1 is an alternative biocontrol agent against B. cereus.